UNDIMINISHED POWER OF IDEOLOGICAL DISTORTION IN RIYANA RIZKI’S SHORT STORY “SUDAH KUKATAKAN, AKU TIMUN MAS” - Khurosan, Herpin Nopiandi; Kristyaningsih, Dyah (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2023)
This study examines how folkloric form in Riyana Rizki's Sudah Kukatakan, Aku Timun Mas (SKATM) becomes the aesthetic strategy at a time when most Indonesian writers deconstruct Ramayana-Mahabharata Epic. Specifically, this study examines the aspects of socially symbolic act, ideologeme, and ideology of form in SKATM. To examine these aspects, the authors laboring political unconscious horizon of interpretation, proposed by Jameson, through three concentric horizons, consisting of the political, social, and historical horizons. The political horizon of interpretation showed that the SKATM narrative is a socially symbolic act of the author over social contradictions that cannot directly be resolved. Additionally, the social horizon of interpretation revealed that the symbolic social actions of SKATM are based on ideologemes or antagonistic social class collective discourses. Later, the historical horizon of interpretation demonstrated that the ideologemes drama at the social level of SKATM are held in a wider space. From the findings, SKATM manifests the folkloric form as a symbolic act, class struggle ideologeme, and cultural revolution